How different forms of policy learning influence each other: case studies from Austrian innovation policy-making. (3rd March 2016) - Biegelbauer, Peter
ABSTRACT: This paper investigates the question whether different forms of policy learning influence each other. The focus is on relationships between different forms of policy learning, which are explored on the basis of case study research in the field of research, technology and innovation policy-making in Austria. Methods utilised are expert interviews and document analysis besides literature and media recherché. With the goal to better understand the mechanisms behind learning processes, different forms of knowledge utilisation are linked to organisation types. The analysis suggests that the introduction of radical policy innovations was possible because different forms of learning were mutually beneficial and enabled actors to reach their goals. Learning about how to obtain political goals provided opportunities to increase the leverage of learning on policy instruments and goals, whilst insights into policies from other countries were also utilised for political learning.